1997
DOI: 10.1530/eje.0.1360369
|View full text |Cite
|
Sign up to set email alerts
|

Results of somatostatin receptor scintigraphy do not predict pituitary tumor volume- and hormone-response to octreotide therapy and do not correlate with tumor histology

Abstract: The value of somatostatin receptor scintigraphy (SRS) to predict the effect of somatostatin analog therapy on pituitary adenomas is not clear, due to the use of different radiopharmaceuticals (123I-Tyr3-octreotide and 111In-pentetreotide) and the small number of patients in previous studies. We used 111In-pentetreotide scintigraphy in 49 patients in order to (i) correlate SRS results with basal tumor volume as well as volume- and hormone-response to 3 months of octreotide therapy (Oct-Tx). (ii) identify tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 0 publications
2
26
0
5
Order By: Relevance
“…Among 48 patients with non-functioning adenomas and gonadotrophinomas (25,26), a significant (.20%) tumour shrinkage was documented in only 7 cases (15%). The SSTR scintigraphy using In111-pentreotide was of poor predictive value in one study (25). A possible explanation of this latter finding is that In111-pentreotide presents with binding affinities towards the SSTR subtypes different from those of octreotide.…”
Section: Discussionmentioning
confidence: 97%
“…Among 48 patients with non-functioning adenomas and gonadotrophinomas (25,26), a significant (.20%) tumour shrinkage was documented in only 7 cases (15%). The SSTR scintigraphy using In111-pentreotide was of poor predictive value in one study (25). A possible explanation of this latter finding is that In111-pentreotide presents with binding affinities towards the SSTR subtypes different from those of octreotide.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, heterodimerisation of the different ssts upon binding would preclude any clear-cut correlation between receptor expression and signal transduction after ligand binding in multiligand SSA (9,10). We have previously demonstrated a lack of correlation between the results of sst scintigraphy (reflecting sst2-status of the adenoma) and the effect of Octreotide on GH secretion or tumour shrinking in acromegaly (59).…”
Section: Somatostatin Receptorsmentioning
confidence: 99%
“…In fact, SRS is used to detect disease sites in neuroendocrine and non-neuroendocrine malignancies (12) and to reveal the presence of activated lymphocytes in inflammatory foci of several autoimmune diseases such as rheumatoid arthritis and Sjo Ègren's disease (13). SRS has been proposed to select candidates responsive to specific peptide treatment (14±16), though in patients with pituitary adenomas this latter evidence is under debate (17,18). A potentially relevant role for SRS in the pretreatment evaluation of TAO has been suggested recently (19) (21) reported that the uptake of 111 In-DTPA-d-Phe 1 -octreotide (measured quantitatively as counts/voxel orbit:brain ratio on filtered, transverse/oblique orbital SPECT reconstruction 4 and 24 h after the injection of 110 MBq radiotracer) was significantly higher in 34 patients with clinically active TAO than in 6 patients with inactive disease and in 10 controls.…”
Section: Somatostatin-receptor Scintigraphy (Srs) In the Pretreatmentmentioning
confidence: 99%